Digital Transformation Strategy for Village-Based Tourism SMEs to Strengthen Sustainable Competitive Advantage - Ilmawan, Faiz Nuha; Maisarah, Sausan Nuhaa (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
This study examines how village-based tourism Micro, Small, and MediumEnterprises (MSMEs) strengthen sustainable competitive advantagethrough digital transformation. Using a qualitative case study approach inDesa Wisata Baturraden, Indonesia, the research integrates ResourceBasedView(RBV),TechnologyAcceptanceModel(TAM),andsustainable competitivenesstheory.Findingsindicatethatdigitaladoption—through smart tourism platforms, financial technology integration, andsustainability-driven branding—significantly enhances operationalefficiency, global visibility, and environmental accountability. However,long-term competitiveness depends on ecosystem-level governance,innovation labs, and continuous digital capability development. The studycontributes to the literature on digital transformation in tourism SMEs byproposing a Village Tourism Digital Hub model to accelerate sustainabledigital maturity.